Role of Religion in Preventing Youth Sexual Activity in Malaysia: A Mixed Methods Study - Muhammad N.A.; Shamsuddin K.; Sulaiman Z.; Amin R.M.; Omar K. (Springer New York LLC, 2024)
One of the popular approaches of preventing youth sexual activity in Malaysia is using religion to promote premarital sexual abstinence. Despite this intervention, youth continue to practise premarital sex. Thus, the purpose of this exploratory mixed methods study was to understand the role of religion on sexual activity among college students in Klang Valley, Malaysia. A self-administered questionnaire survey to determine the relationship between religiosity and youth sexual activity was carried out on 1026 students recruited from 12 randomly selected colleges. Concurrently, face-to-face interviews were conducted on 15 students to explore how religiosity had influenced their decision on sexual activity. The survey data were analysed using logistic regression, while the qualitative data from the interviews were examined using thematic analysis with separate analysis for each gender. Both quantitative and qualitative results were then compared and integrated. Religious activity significantly reduced the risk of continuing sexual activity among female students (AOR = 0.67, CI = 0.47, 0.95, p = 0.02) but not male students. There was no significant relationship of religious affiliation and intrinsic religiosity (inner faith) to sexual activity by gender. Having faith in religion and strong sexual desire were the main themes that explained participants’ sexual behaviour. Engaging in religious activity might be effective at preventing female students from being sexually active. However, when sexual urges and desires are beyond control, religiosity might not be effective.